Pengaruh Kinerja Keuangan Terhadap Harga Saham Melalui Price To Book Value Sebagai Variabel Mediasi pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia Tahun 2024 - Firmansyah Khudori; Aty Herawati (Ikatan Da'i Indonesia, 2025)
This study aims to analyze the effect of financial ratios, including Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Earning per Share (EPS), on stock prices with Price to Book Value (PBV) as an intervening variable. The research sample consists of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2024 period.The analytical method employed is Path Analysis using SPSS software. The results reveal that CR has no effect on PBV or stock prices, suggesting that liquidity is not a major consideration for investors. DER positively affects PBV but has a direct negative effect on stock prices, while indirectly influencing them positively through PBV. ROA positively affects PBV but has a direct negative effect on stock prices and a positive effect through PBV. EPS negatively affects PBV butdirectly has a positive effect on stock prices and a negative effect through PBV. TATO negativelyaffects both PBV and stock prices, both directly and indirectly. Furthermore, PBV significantly and positively affects stock prices, confirming its role as a key mediating variable.This study emphasizes that PBV serves as a strong indicator in mediating the relationship between financial performance and stock prices. The results are expected to provide valuable insights for investors in making investment decisions and for companies in evaluating their financial strategies.